HAK KHIYAR AL TADLIS DALAM TRANSAKSI JUAL BELI SEPEDA MOTOR BEKAS: PERSPEKTIF IMAM AL SHARKASI - Asnita, Dessy; Rauzi, Muhammad; Dwi Kurnia, Ryzka (Program Studi Hukum Keluarga dan Hukum Ekonomi Syariah, Program Pascasarjana Institut Agama Islam Negeri (IAIN) Ternate, 2023)
The subject of this research is the responsibility of khiyar al-tadlis in the process of sale and purchase of used motorcycles in Gampong Kemuning Peureulak Perspective Al Sharkasi. To analyze the data on the research has been used Qualitative Descriptive Analysis. As for this research, the results have shown that the sale transactions in Gampong Keumeng are performed orally regarding the price and conditions. However, the written transaction begins after the price is settled. Negotiations use easy-to-understand words so consumers can understand what to do when a transaction occurs. It's usually accepted both by the seller and buyer. In the practice of buying used motorcycles in the Gampong Keumuneng, the linen used is a linen. Because the damage was decided after the obstacle was made. According to Imam Al Sharkasi, if the buyer finds out the defect of the goods when making a transaction, the transaction is valid and there is no right of choice or deference afterwards because the purchaser accepts the circumstances with the condition of such goods.